The adhesion GPCR ADGRL2 engages Gα13 to enable epidermal differentiation - Xue Yang; Feng He; Vanessa Lopez-Pajares; Douglas F. Porter; Krassimira Garbett; Zurab Siprashvili; Luca Ducoli; Robin M. Meyers; David L. Reynolds; Duy Lan Huong Bui; Audrey Hong; Duy Thanh Nguyen; et al. (Proceedings of the National Academy of Sciences, 2025)
Homeostasis relies on signaling networks controlled by cell membrane receptors. Although G-protein-coupled receptors (GPCRs) are the largest family of transmembrane receptors, their specific roles in the epidermis are not fully understood. Dual CRISPR-Flow and single cell Perturb RNA-sequencing knockout screens of all epidermal GPCRs were thus performed, uncovering an essential requirement for adhesion GPCR ADGRL2 (latrophilin 2) in epidermal differentiation. Among potential downstream guanine nucleotide-binding G proteins, ADGRL2 selectively activated Gα13. Follow-up tissue knockouts verified that Gα13 is also required for epidermal differentiation. A cryoelectron microscopy structure in lipid nanodiscs showed that ADGRL2 engages with Gα13 at multiple interfaces, including via an interaction between ADGRL2 intracellular loop 3 and a Gα13-specific QQQ glutamine triplet sequence in its GTPase domain. In situ gene mutation of this interface sequence impaired epidermal differentiation, highlighting an essential new role for an ADGRL2-Gα13 axis in epidermal differentiation.